The Role of Human Resource Management in Sustaining or Advancing: A Review of Compensation Systems and Low-Wage Employment - Heru Subiyantoro; Karnaji Karnaji; Fendy Suhariadi (Dinasti International Journal of Education Management And Social Science, 2024)
This study examines compensation systems in low-wage employment, focusing on their design, organizational rationale, and outcomes for employers within the context of Human Resource Management. Utilizing a qualitative literature review method, the research analyzes secondary data from sources like Scopus and Google Scholar to provide insights into compensation trends in low-wage sectors. The findings show that compensation systems in these jobs are typically structured to minimize organizational costs, offering low wages, limited benefits, and minimal employee development opportunities. These designs lead to challenges for workers, such as financial insecurity, job dissatisfaction, and restricted career advancement, while organizations face high turnover, decreased productivity, and reduced employee engagement. Although these strategies provide short-term cost savings, they create long-term challenges for workforce stability. The study emphasizes the importance of designing compensation systems that balance organizational needs with employee well-being, ultimately contributing to sustainable workforce development and improved organizational outcomes.